EGG WHITE ALBUMIN FORM COMPLEX WITH ASPIRIN AND CAFFEINE AND ITS ROLE AS FREE RADICAL SCAVENGER - Jayanti, Gatra Ervi; Widyarti, Sri; Sabarudin, Akhmad; Sumitro, Sutiman Bambang (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Egg white protein (ovalbumin) is well known to be freshly consumed in Indonesia as traditional medicine, or it is usually known as Jamu.â€ Ovalbumin, as well as egg white albumin, is able to form complex compounds with other substances through the formation of weak chemical and physical bonds. The objective of this study is to understand the behavior of ovalbumin as radical scavenger when it binds to antioxidants such as aspirin and caffeine (as a complex). Methods: In this study, docking sites and ovalbumin as scavenger were studied using computer-modeling software. An ovalbumin was used only for computer modeling, whereas in the wet laboratory, the freeze-drying albumin was used for electron spin resonance (ESR) and Fourier transform-infrared (FTIR) spectroscopy to determine its ability as a scavenger and functional groups, respectively. Albumin solution was applied to measure the viscosity. Results: The variability of tridimensional structures of aspirin was investigated after binding with ovalbumin. However, these structures cannot be seen clearly on caffeine. The root-mean-square deviation analysis showed that aspirin, as well as caffeine, altered the dynamic conformation of ovalbumin. The complex of aspirin-ovalbumin-caffeine which was treated at a temperature of âˆ’70Â°C showed intermolecular force. ESR results showed that the complex compounds could effectively reduce more free radicals when compared to aspirin or caffeine. The existence of aromatic compounds (as confirmed by FTIR) was useful for the scavenger molecules and chemical interaction occurs. The viscosity of the complex was similar with normal gastric mucus, which associated with radical scavenger. Conclusion: The characters of albumin when it binds to aspirin and caffeine indicated that scavenging activity of the complex and the viscosity showed an important result to be physiological scavengers of free radicals.Â Â